Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae) - Zhao, Chao; Wang, Zhaohong; Tong, Xiaoli (Zootaxa, 2018)
Bamboosiella caudibruna sp. n., B. rugata sp. n. and B. sculpta sp. n. are described and illustrated from China. In addition, B. brevis Okajima, B. lewisi (Bagnall) and B. xiphophora Okajima are newly recorded from this country. A key for identification of seventeen Chinese Bamboosiella species is provided.